Brachial supporting structure of Spiriferida (Brachiopoda). (May 2021) - Yuan, Zhiwei; Guo, Wen; Lyu, Dan; Sun, Yuanlin
Abstract: The filter-feeding organ of some extinct brachiopods is supported by a skeletal apparatus called the brachidium. Although relatively well studied in Atrypida and Athyridida, the brachidial morphology is usually neglected in Spiriferida. To investigate the variations of brachidial morphology in Spiriferida, 65 species belonging to eight superfamilies were analyzed. Based on the presence/absence of the jugal processes and normal/modified primary lamellae of the spiralia, four types of brachidium are recognized. Type-I (with jugal processes) and Type-II (without jugal processes), both having normal primary lamellae, could give rise to each other by losing/re-evolving the jugal processes. Type-III, without jugal processes, originated from Type-II through evolution of the modified lateral-convex primary lamellae, and it subsequently gave rise to Type-IV by evolving the modified medial-convex primary lamellae. The evolution of brachidia within individual evolutionary lineages must be clarified because two or more types can be present within a single family. Type-III and Type-IV are closely associated with the prolongation of the crura, representing innovative modifications of the feeding apparatus in response to possible shift in the position of the mouth towards the anterior, allowing for more efficient feeding on particles entering the mantle cavity from the anterior gape. Meanwhile, the modified primary lamellae adjusted/regulated the feeding currents. The absence of spires in some taxa with Type-IV brachidium might suggest that they developed a similar lophophore to that in some extant brachiopods, which can extend out of the shell.